Integrating CRISPR-Cas and Next Generation Sequencing in Plant Virology - Mushtaq, Muntazir; Dar, Aejaz Ahmad; Basu, Umer; Bhat, Basharat Ahmad; Mir, Rakeeb Ahmad; Vats, Sanskriti; Dar, M. S.; Tyagi, Anshika; Ali, Sajad; Bansal, Monika; Rai, Gyanendra Kumar; Wani, Shabir Hussain (Frontiers in Genetics, 2021)
Plant pathology has been revolutionized by the emergence and intervention of next generation sequencing technologies (NGS) which provide a fast, cost-effective and reliable diagnostic for any class pathogens. NGS has made tremendous advancement in the area of research and diagnostics of plant infecting viromes and has bridged plant virology with other advanced research fields like genome editing technologies. NGS in a broader perspective holds the potential for plant health improvement by diagnosing and mitigating the new or unusual symptoms caused by novel/unidentified viruses. viral genomes. CRISPR-based genome editing technologies can enable rapid engineering of efficient viral/viroid resistance by directly targeting specific nucleotide sites of plant viruses and viroids. Critical genes such as eIf (iso) 4E or eIF4E have been targeted via CRISPR platform to produce plants resistant to single-stranded RNA (ssRNA) viruses. CRISPR/Cas-based multi-target DNA or RNA tests can be used for rapid and accurate diagnostic assays for plant viruses and viroids. Integrating NGS with CRISPR-based genome editing technologies may lead to paradigm shift in combating deadly disease-causing plant viruses/viroids at the genomic level. Furthermore, newly discovered CRISPR/Cas13 system has unprecedented potential in plant viroid diagnostics and interference. In this review, we have highlighted the application and importance of sequencing technologies on covering the viral genomes for precise modulations. This review also provides a snapshot vision on emerging developments in NGS technologies for the characterization of plant viruses and their potential utilities, advantages, and limitations in plant viral diagnostics. Furthermore, some of the notable advances like novel virus-inducible CRISPR/Cas9 system that confers virus resistance with no off-target effects have been discussed.